O SOL NAS OBRAS MODERNISTAS CEARENSES - ANÁLISE DE DUAS EDIFICAÇÕES REFERENCIAIS - Raviolo, Bruno de Paiva Y; Leite, Renan Cid Varela; Homem Filho, Ademir de Oliveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The shading of openings and natural ventilation are two of the foremost passive strategies when adapting buildings to hot and humid climate. During the 70's the modernist movement in Fortaleza produced buildings that applied brise-soleil seen both as compositive element and as instrument to reduce internal heat gains. Noticing the ever more requiring comfort and energy standards and the development of computational tools to help during design process, this paper analyzes the brise-soleil efficacy on the facade of two public service buildings designed by modernist architects pertaining to the office typology. Research methods includes case studies and computational simulations. Global radiation analyses were employed at volumetric studies. Buildings were modelled and their shading elements detailed. Shadow masks were created to quantify hours of shading as well as unprotected hours of direct insolation. Building orientation as design criteria are further discussed, as well the adequacy of their facade treatment.